Silk Road to the Sahel: African Ambitions in China's Belt and Road Initiative - Yunnan Chen (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2018)
This paper by Yunnan Chen explores the Belt and Road Initiative, which has become a centerpiece of China's foreign economic policy. While it primarily focused on the Eurasian region, the BRI has salient implications for African development and regional integration, accelerating existing infrastructure and industrial cooperation and contributing to African industrialization strategies. However, rapid expansion of infrastructure lending also brings risks in its debt burdens, sustainability impacts, and economic viability.
Keywords: 330